INCIDENCE OF EXTENDED SPECTRUM BETA-LACTAMASE PRODUCING ENTEROBACTERIACEAE IN RAW VEGETABLES SOLD IN DISTRICT KOHAT (Journal of Medical & Health Sciences Review, 2025)
Background: Extended spectrum β-lactamase (ESBL) producing bacteria is a growing public health concern globally because it shows resistance to β-lactam antibiotics. The consumption of contaminated food products, particularly raw vegetables, is a significant contributing factor to the spread of these bacteria. This study investigates the occurrence of ESBL producing bacteria in raw vegetables retailed in the District of Kohat. 80 Samples of raw vegetables were collected from wholesale markets, retail shops and small vendors in the District of Kohat, and the bacterial strains were identified as E. coli and Klebsiella pneumoniae.Materials and Methods: Colony-forming unit (CFU) estimation, Gram staining, biochemical testing, most probable number (MPN) analysis, and the double disc synergy test to detect ESBL production were some of the procedures included in the study approach.Results: The coliform counts in raw vegetables were found to range from 25-45×106 CFU/g. Different commercially available antibiotics were used to determine their potency against the tested bacterial isolates (E. coli and K. pneumoniae). Klebsiella pneumoniae displayed resistance against Ampicillin AP (10µg) and Cefoxitin FOX (30 µg) antibiotics. In contrast, E. coli showed sensitivity to all antibiotics except Cefoxitin FOX (30 µg). Additionally, the study also estimated the Most Probable Number (MPN) value of coliforms in raw vegetables. The MPN value provides an estimate of the number of viable bacteria present in a sample. In this study, the highest MPN value was recorded in Tomato (T 1) having MPN index per 100 mL was 33, while the lowest MPN value was for Lettuce (L 3) having MPN index per 100 mL was 4. The high MPN value indicates a higher risk of contamination with fecal matter.Conclusion: In conclusion, our study identified the presence of ESBL producing E. coli and Klebsiella pneumoniae in raw vegetables retailed in the District of Kohat. Among these, E. coli was detected in 12 samples (15%) while Klebsiella pneumoniae was detected in 8 samples (10%). The antibiotic resistance of these bacteria suggests a potential risk to public health. Therefore, it is essential to implement proper food safety practices programs to prevent the spread of these bacteria.